DEVELOPING A FACIAL ANALYSIS ALGORITHM IN MATLAB: TECHNIQUES AND APPROACHES (Web of Teachers: Inderscience Research, 2025)
Facial analysis has emerged as a cornerstone in fields ranging from security and healthcare to entertainment and social interaction. This article delves into the development of a robust facial analysis algorithm using MATLAB, a powerful tool for numerical computing and image processing. By combining theoretical insights with practical examples, it explores essential techniques such as face detection, feature extraction, and image enhancement. Readers will also discover innovative approaches leveraging MATLAB’s Computer Vision Toolbox and machine learning capabilities to create applications that recognize, analyze, and even "admire" human faces.